2013
DOI: 10.1590/s0100-204x2013000500003
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fluxes from irrigated common‑bean as affected by mulching and mineral fertilization

Abstract: Index terms: Cerrado, climate change, greenhouse gas, N fertilization, nitrous oxide, no-tillage. Fluxos de nitrogênio em feijoeiro irrigado influenciados pela cobertura morta e a fertilização mineralResumo -O objetivo deste trabalho foi medir os fluxos de N 2 O-N e NH 3 -N, ao longo de uma safra de feijoeiro irrigado (Phaseolus vulgaris), influenciados pelo uso ou não de cobertura morta e fertilização mineral. Termos para indexação: Cerrado, mudanças climáticas, gas de efeito estufa, óxido nitroso, plantio di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Luizão et al 1989). In irrigation experiments by Vasconcelos et al (2004) and Carvalho et al (2013), N 2 O fluxes increased after irrigation during the dry season in Brazil. Luizão et al (1989) and Sotta et al (2008) reported that finer textured soils have a higher N availability.…”
Section: Introductionmentioning
confidence: 91%
“…Luizão et al 1989). In irrigation experiments by Vasconcelos et al (2004) and Carvalho et al (2013), N 2 O fluxes increased after irrigation during the dry season in Brazil. Luizão et al (1989) and Sotta et al (2008) reported that finer textured soils have a higher N availability.…”
Section: Introductionmentioning
confidence: 91%
“…The absence of a significant effect of WB amendment on N 2 O fluxes was probably linked to the physical structure of the clay Ferralsol and the aerobic nature of the cropping system. Under well-drained conditions, there is no accumulation of water on the soil surface and the major part of the mineral N applied as top dressing could be lost by ammonia volatilization (Carvalho et al, 2013b). Verhoeven and Six (2014) observed no effect of biochar on N 2 O fluxes under aerobic conditions either.…”
Section: Determining Factors and Potential Effects Of Biochar On Soilmentioning
confidence: 97%
“…In contrast to the Amazon and Atlantic forests, where N 2 O emissions range from 0.38 to 16 kg ha -1 , with the highest value in the Amazon forest, and the maximum emission of the Atlantic forest is below 3.42 kg ha -1 (Meurer et al, 2016). Soils under natural Cerrado vegetation showed very low and even negative values, with a median emission of 0.14 kg ha -1 and often below the detection limit, as shown in several studies (Metay et al, 2007;Cruvinel et al, 2011;Bustamante et al, 2012;Carvalho et al, 2013;Martins et al, 2015;Santos et al, 2016;Silva et al, 2017;Sato et al, 2017;Oliveira Filho et al, 2020).…”
Section: Continuementioning
confidence: 80%
“…Among the different factors affecting N 2 O emissions in agricultural soils, the conversion of native Cerrado vegetation to agroecosystems favors the emission of N 2 O to the atmosphere, under sugarcane cropping systems (Silva et al, 2017), integrated cropping-livestock production, no-till and conventional tillage (Martins et al, 2015;Sato et al, 2017). In addition, N 2 O emissions are usually associated with soil moisture (Carvalho et al, 2013;Santos et al, 2016) and nitrogen fertilizer application (Carvalho et al, 2016;Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%